Study on atomization characteristics of nozzles in artificial snow making process - 李睿; 刘斌; 胡恒祥; 李卓睿; 曾涛 (Zhileng xuebao)
The increasing global warming and rapid growth of the ski industry have raised higher demands for artificial snowmaking technology and snow quality, with the quality of artificial snowmaking closely linked to the atomization characteristics of snowmaking nozzles.In this paper, the influence of different nozzle interference and gas-liquid mass mixing ratio (GLR) on droplet size distribution and collision mechanism in spray field is studied.The nozzle spacing (D) represents the degree of interference between nozzles, while the gas-liquid mass mixing ratio (GLR) signifies varying degrees of mixing disturbance under identical nozzles.The velocity and size distribution of droplets in the spray field were measured using a laser particle size measuring instrument and a high-speed camera, while the fragmentation and collision of droplets in the spray field were analyzed based on Weber number (We).The results indicate that the axial velocity of double nozzles exceeds that of single nozzles at varying spacing intervals. Specifically, when the nozzle spacing is 10 cm and 15 cm, the peak axial velocities are recorded as 5.6 m/s and 5.5 m/s respectively.The droplet size undergoes a non-monotonic variation with axial distance due to the competing effects of fragmentation and coalescence, initially decreasing before increasing.The interaction between the spray fields of two nozzles enhances droplet collision, resulting in a higher We number compared to that of individual nozzles. The analysis of the flow field of double nozzles under different arrangement conditions reveals that a higher level of uniformity in particle size distribution is observed when GLR=0.10 and D=15cm.